Non motor symptoms in progressive supranuclear palsy: prevalence and severity. (December 2017) - Radicati, Fabiana; Martinez Martin, Pablo; Fossati, Chiara; Chaudhuri, Kallol Ray; Torti, Margherita; Rodriguez Blazquez, Carmen; Vacca, Laura; Stocchi, Fabrizio
Abstract NMSs have been extensively studied in PD patients but not in other forms of parkinsonism such as Progressive Supranuclear Palsy (PSP). The primary objective of this study was to analyze the frequency, severity and the type of non-motor symptoms (NMS) in PSP patients using the non-motor symptoms scale (NMSS). The secondary objective was to differentiate NMS between PSP and Parkinson's disease (PD). We enrolled in this cross-sectional study 50 consecutive PSP and 100 matched Parkinson's disease (PD) patients, in the proportion PSP/PD = 1/2, matched in age, sex, and disease duration. Motor and Non Motor symptoms (different scales for each disease) were evaluated at baseline using PSP scale, SCOPA Motor, Montreal Cognitive Assessment (MOCA), HADS, Hamilton, and Non Motor Symptom scale (NMSS). Comparative analysis was done using chi-squared test, Mann-Whitney test and Fisher's exact test. Fifty PSP (56% female) and 100 PD (59% female) patients completed the study protocol and were included for statistical analysis. The NMSS total domains score in the PSP group was 77.58 ± 42.95 (range 14–163) with NMS burden grade: 4, very severe, and the in the PD group was 41.97 ± 35.45 (range: 0–215) with NMS burden grade: 3, severe. The comparative analysis showed that NMS total score (p < 0.0001), Sleep/Fatigue (p = 0.0007), Mood/Apathy (p = 0.0001), Gastrointestinal (p < 0.0001), and Urinary dysfunction (p = 0.0001) domains were significantly more severe in PSP patients than in PD. This observational study reports that NMSs are very frequent in PSP patients hence the higher burden of NMS in PSP specifically related to mood/apathy, attention/memory, gastrointestinal, urinary disturbances compared to PD. Parkinsonism: understanding the non-motor symptom burden Non-motor symptoms are more frequent and severe in patients with Progressive Supranuclear Palsy (PSP) than in those with Parkinson's disease (PD). An international team led by Fabrizio Stocchi at the Institute for Research and Medical Care IRCCS in Rome used the Non-motor Symptoms Scale (NMSS) to compare the symptoms experienced by 50 PSP patients and 100 PD patients. They found that patients with PSP suffered worse and more frequent gastrointestinal and urinary disturbances, as well as more severe dysfunctions in attention and memory compared with PD patients. Moreover, the reported lack of motivation and sleep disturbances were more burdensome in PSP patients. These findings will not only contribute to diagnose PSP earlier and more accurately, but also help to increase awareness of the impact of non-motor symptoms on patients' quality of life.